2019
DOI: 10.1371/journal.pntd.0007567
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency is a potential risk factor for lipid Amphotericin B nephrotoxicity

Abstract: Invasive fungal infections (IFI) is a worldwide serious health problem and Amphotericin B (AmB) has been considered the drug of choice for IFI treatment. Despite its efficacy, clinical use of AmB has been associated with renal toxicity. Some lines of evidence have shown that an extemporaneous lipid emulsion preparation of AmB (AmB/LE) was able to attenuate nephrotoxicity, presenting similar benefits at a lower cost. Studies have been demonstrating that hypovitaminosis D may hasten the progression of kidney dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(50 reference statements)
1
5
0
3
Order By: Relevance
“…In addition to the well-known risk factors related to the CKD progression, other studies have been highlighting the hypovitaminosis D as a non-traditional aggravating factor for renal diseases (4-8, 31, 32). Previously, we demonstrated that VDD not only impaired the recovery but also accelerated the renal disease progression, exerting an important role on the process of RFF in different experimental models (4)(5)(6)(7)(8)(9)31). Although most studies have been focusing their efforts on the mechanisms underlying RFF, there is a lack of effective anti-fibrotic therapies which could efficiently block or reverse the progression of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the well-known risk factors related to the CKD progression, other studies have been highlighting the hypovitaminosis D as a non-traditional aggravating factor for renal diseases (4-8, 31, 32). Previously, we demonstrated that VDD not only impaired the recovery but also accelerated the renal disease progression, exerting an important role on the process of RFF in different experimental models (4)(5)(6)(7)(8)(9)31). Although most studies have been focusing their efforts on the mechanisms underlying RFF, there is a lack of effective anti-fibrotic therapies which could efficiently block or reverse the progression of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Em estudo sobre fatores de risco para IRA em UTI, observou-se que 7,5% dos pacientes apresentaram HAS (2,22) , IC, hipovolemia, uso de drogas vasoativas, como a noradrenalina, a dobutamina, a dopamina e o uso de antibióticos (2,11,24) . Concluiu-se que ter três ou mais fatores de risco associados aumentavam a possibilidade de desenvolvimento da doença (2) .…”
Section: Discussionunclassified
“…A utilização de drogas nefrotóxicas e a hipovolemia eram suas principais causas. Atualmente, outros fatores etiológicos contribuem para o seu desenvolvimento, incluindo eventos iatrogênicos, como a hipotensão arterial durante as cirurgias, diarreia intensa secundária à infecção fúngica, em especial por Clostridium difficile, uso de antibióticos nefrotóxicos (anfotericina B, aminoglicosídeos), anti-inflamatórios não esteroides (AINEs), infecções, sepse, uso de contrastes para procedimentos diagnósticos (como cinecoronarioangiografia, tomografias, ressonância magnética), afecções cardiovasculares (principalmente IC, IAM), idade avançada, sexo masculino, localização geográfica e condição socioeconômica, que inclusive modificam consideravelmente os dados epidemiológicos e eventos futuros da doença (11) .…”
Section: Introductionunclassified
“…Four-mm histological sections of renal tissue were stained with hematoxylin-eosin and examined under light microscope. For the evaluation of renal damage, 20-30 grid fields (x400 magnification) measuring 0.245 mm 2 were evaluated by graded scores, according to the following criteria: (0), less than 5% of the field showing tubular epithelial swelling, vacuolar degeneration, inflammatory infiltrate, necrosis and desquamation; (1), 5-25% of the field presenting renal lesions; (2), involvement of 25-50% with renal damage; (3), 50-75% of damaged area; (4), more than 75% of the grid field presenting renal lesions (n = 8 mice per group) [20].…”
Section: Light Microscopymentioning
confidence: 99%